Perceived pain extent is associated with disability, depression and self‐efficacy in individuals with whiplash‐associated disorders. (6th May 2016) - Falla, D.; Peolsson, A.; Peterson, G.; Ludvigsson, M.L.; Soldini, E.; Schneebeli, A.; Barbero, M.
Abstract: Background: Completion of a pain drawing is a familiar task in those presenting with whiplash‐associated disorders (WAD). Some people report pain almost over their entire body. Yet the reasons for larger pain extent have not been fully explored. Methods: A novel method was applied to quantify pain extent from the pain drawings of 205 individuals with chronic WAD. Pain extent was evaluated in relation to sex, age, educational level, insurance status and financial status. Multiple linear regression analysis was used to verify whether pain extent was associated with other health indicators including perceived pain and disability, health‐related quality of life, pain catastrophizing, anxiety, depression and self‐efficacy. Results: Pain extent was influenced by sex (χ 2 :10.392, p < 0.001) with larger pain extent in women compared to men (7.88 ± 7.66% vs. 5.40 ± 6.44%). People with unsettled insurance claims (χ 2 : 7.500, p < 0.05) and those with a worse financial situation (χ 2 :12.223, p < 0.01) also had larger pain extent. Multiple linear regression models revealed that, when accounting for age, sex, education, insurance status, financial status and neck pain intensity, pain extent remained associated with perceived disability ( p < 0.01), depression ( p < 0.05) and self‐efficacy ( p < 0.001). Conclusion: By utilizing a novel method for pain extent quantification, this study shows that widespread pain is associated with a number of factors including perceived disability, depression and self‐efficacy in individuals with chronic WAD. Widespread pain should alert the clinician to consider more specific psychological screening, particularly for depression and self‐efficacy, in patients with WAD. What does this study add?: Women with chronic WAD, those with unsettled insurance claims and those with poorer financial status perceive more widespread pain. When controlling for these factors, larger pain areas remain associated with perceived pain and disability, depression and self‐efficacy. The pain drawing is useful to support psychological screening in people with chronic WAD.